Stitches a memoir... - Small, David 1945- (New York W.W. Norton & Co., 2009)
"In Stitches, Small, the award-winning children's illustrator and author, re-creates this terrifying event in a life story that might have been imagined by Kafka. As the images painfully tumble out, one by one, we gain a ringside seat at a gothic family drama where David-- a highly anxious yet supremely talented child-- all too often became the unwitting object of his parents' buried frustration and rage." -- Provided by publisher
FA-2933g donated by Acquisition Section University Library.
Keywords: Small, David -- 1945- -- Comic books, strips, etc; Authors, American -- 20th century -- Biography -- Comic books, strips, etc; Artists -- United States -- Biography -- Comic books, strips, etc; Children's stories -- Illustrations -- Comic books, strips, etc; Children's stories -- Authorship -- Comic books, strips, etc